2016
DOI: 10.20524/aog.2016.0077
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines and the role of visceral adipose tissue in inflammatory bowel disease

Abstract: Recently, adipocytes have been recognized as actively participating in local and systemic immune responses via the secretion of peptides detectable in relevant levels in the systemic circulation, the so-called “adipo(cyto)kines”. Multiple studies appearing within the last 10-15 years have focused on the possible impact of adipose tissue depots on inflammatory bowel disease (IBD). Consequently, various hypotheses regarding the role of different adipokines in inflammatory diseases in general and in intestinal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 163 publications
(183 reference statements)
1
26
0
Order By: Relevance
“…Hyaluronidase treatment inhibits tissue inflammation. The production of adipokines and antimicrobial peptides by adipocytes has been hypothesized to be important to both promote inflammation and protect against infection (16,20). Therefore, given observations that hyaluronidase can inhibit adipogenesis and directly modulate several immune responses, we next examined the effect of hyaluronidase on the inflammatory response of both skin and colon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyaluronidase treatment inhibits tissue inflammation. The production of adipokines and antimicrobial peptides by adipocytes has been hypothesized to be important to both promote inflammation and protect against infection (16,20). Therefore, given observations that hyaluronidase can inhibit adipogenesis and directly modulate several immune responses, we next examined the effect of hyaluronidase on the inflammatory response of both skin and colon.…”
Section: Resultsmentioning
confidence: 99%
“…The biological significance of increased fat accumulation surrounding sites of epithelial injury to the colon was previously unknown. Though visceral adipose tissue has long been speculated to be a component of the innate immune system of the gut (35), and several descriptions of the production of "adipokines" from fat such as leptin, adiponectin, and cytokines have been reported (36), the contribution of adipokines to IBD has been controversial (20,37). We propose here that recent observations of reactive adipogenesis in the skin can be applied to also understand the significance of adipogenesis in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, functional adipocytic NF-κB signal transduction is a prerequisite for healthy adipose tissue remodeling, thus further proving its important role in obesity (Wernstedt Asterholm et al 2014). Thus, adipocytic TLR9-dependent signaling -especially within the visceral adipose tissue depot -can be postulated to serve important homeostatic functions (Kwon et al 2014, Karrasch & Schaffler 2016, especially in the context of over-nutrition and obesity. Recent studies demonstrated that cell-free DNA as well as so-called extracellular traps (consisting of nucleic acids and anti-microbial peptides derived from macrophages and neutrophil granulocytes) are increased in obesity and activate macrophages as well as dendritic cells in a TLR9-and TLR7-dependent manner independent of specific CpG-oligodeoxynucleotides (Nishimoto et al 2016, Revelo et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Excess secretion of adipocytokine and macrophage recruitment are features of obesity‐related systemic inflammation which lead to low‐grade chronic inflammation . Even in early disease stages visceral fat surrounding diseased non‐malignant bowel, such as in Crohn's disease patients, has been shown to contain localized inflammation . These complex relationships between obesity and inflammation may explain the different associations in patients undergoing cancer surgery and those having surgery for benign conditions.…”
Section: Discussionmentioning
confidence: 99%